2017
DOI: 10.1038/srep42909
|View full text |Cite
|
Sign up to set email alerts
|

β-globin gene cluster haplotypes in ethnic minority populations of southwest China

Abstract: The genetic diversity and relationships among ethnic minority populations of southwest China were investigated using seven polymorphic restriction enzyme sites in the β-globin gene cluster. The haplotypes of 1392 chromosomes from ten ethnic populations living in southwest China were determined. Linkage equilibrium and recombination hotspot were found between the 5′ sites and 3′ sites of the β-globin gene cluster. 5′ haplotypes 2 (+−−−), 6 (−++−+), 9 (−++++) and 3′ haplotype FW3 (−+) were the predominant haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moreover, the Hb Rush variant in the different Chinese families was linked to a common β-globin gene cluster haplotype [+----+-], thus suggesting a common origin of the variant in the populations of Southwest China, presumably owing to a founder effect. However, the haplotype [+----+-] is a prevalent haplotype that is associated with thalassemia and normal β-globins in the region [22], it may be generated by recombination and gene conversion events [23]. Therefore, our findings do not exclude the possibility that the unstable Hb Rush variant might have arisen more than once in Chinese populations.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the Hb Rush variant in the different Chinese families was linked to a common β-globin gene cluster haplotype [+----+-], thus suggesting a common origin of the variant in the populations of Southwest China, presumably owing to a founder effect. However, the haplotype [+----+-] is a prevalent haplotype that is associated with thalassemia and normal β-globins in the region [22], it may be generated by recombination and gene conversion events [23]. Therefore, our findings do not exclude the possibility that the unstable Hb Rush variant might have arisen more than once in Chinese populations.…”
Section: Discussionmentioning
confidence: 72%
“…The β 3.5 kb deletion chromosome was found to be closely related to haplotype H2, with only one change (rs77526129 ( Hinc II‐5′ε)) from the ancestral haplotype. For comparison of the β A haplotype, previously reported information was also listed, as shown in Table 3 (Aggarwal et al., 2013; Callegari‐Jacques et al., 2007; Chan et al., 1986; Fucharoen et al., 2002; Long et al., 1990; Shimizu et al., 2004; Shimizu et al., 2008; Shimizu et al., 2006; Sun et al., 2017). The result showed that haplotype H2 is the most frequent haplotype in Thai, Chinese, Indians, other Asian, European, and American Indian populations, except in the African population.…”
Section: Resultsmentioning
confidence: 99%
“… a Data from Fucharoen et al, 2002; b data from Aggarwal et al, 2013; c data from Chan et al, 1986; d data from Shimizu et al, 2008; e data from Sun et al, 2017; f data from Shimizu et al, 2006; g data from Shimizu et al, 2004; h data from Long, Chakravarti, Boehm, Antonarakis, & Kazazian, 1990; i data from Callegari‐Jacques et al, 2007. The symbols (‐ or +) indicate the absent (‐) or present (+) of each polymorphic site, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations